Post-transcriptional Regulation through Long Noncoding RNAs (lncRNAs) - Ladomery, Michael; Pisignano, Giuseppina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of eight articles, of which seven are reviews and one is a research paper, that together form a Special Issue that describes the roles that long noncoding RNAs (lncRNA) play in gene regulation at a post-transcriptional level.